Age, growth, reproductive biology and diet of Spondyliosoma emarginatum (Cuvier 1830) in the West Coast National Park, South Africa - Fairhurst, Lucinda (Department of Biological Sciences, 2014)
Includes bibliographical references (leaves 47-50).